N (6)‐Isopentenyladenosine in RNA Determines the Cleavage Site of Endonuclease Deoxyribozymes - Liaqat, Anam (Angew Chem Int Ed Engl, 2020)
RNA‐cleaving deoxyribozymes can serve as selective sensors and catalysts to examine the modification state of RNA. However, site‐specific endonuclease deoxyribozymes that selectively cleave post‐transcriptionally modified RNA are extremely rare and their specificity over unmodified RNA is low. We report that the native tRNA modification N(6)‐isopentenyladenosine (i(6)A) strongly enhances the specificity and has the power to reconfigure the active site of an RNA‐cleaving deoxyribozyme. Using in vitro selection, we identified a DNA enzyme that cleaves i(6)A‐modified RNA at least 2500‐fold faster than unmodified RNA. Another deoxyribozyme shows unique and unprecedented behaviour by shifting its cleavage site in the presence of the i(6)A RNA modification. Together with deoxyribozymes that are strongly inhibited by i(6)A, these results highlight that post‐transcriptional RNA modifications modulate the catalytic activity of DNA in various intricate ways.